Molecular assessment of splicing variants in a cohort of patients with inborn errors of immunity: methodological approach and interpretation remarks - Miguel Berenguel, Laura; Gianelli, Carla; Matas Pérez, Elisabet; del Rosal, Teresa; Méndez Echevarría, Ana; Robles Marhuenda, Ángel; Feito Rodríguez, Marta; Caballero Molina, Maria Teresa; Magallares García, Lorena; Sánchez Garrido, Brenda; Hita Díaz, Samantha; Allende Martínez, Luis; et al. (Frontiers in Immunology, 2025)
BackgroundSplicing is the molecular mechanism to produce mature messenger RNA (mRNA) before its translation into protein. It is estimated that 50% of disease-causing mutations disrupt splicing, mostly of them affecting canonical positions. However, variants occurring in coding regions or deep-intronic variants can also affect splicing. In these cases, interpretation of the results may be challenging and molecular validation is required.MethodsThe study includes 23 patients with splicing variants out of a cohort of 187 patients diagnosed with inborn errors of immunity (IEI). Clinical features and immunophenotypes are shown. Reverse transcription-polymerase chain reaction (RT-PCR) is the molecular assay employed for pathogenicity validation.ResultsWe detected 23 patients of 20 pedigrees with splicing variants in IEI genes, which constitutes the 12.3% of our cohort. In total, 21 splicing variants were analyzed, 10 of which had previously been reported in the literature and 11 novel ones. Among the 23 patients, 16 showed variants at canonical splice sites. Molecular validation was required only in the cases of genes of uncertain significance (GUS), high homology pseudogenes or incompatible clinical phenotype. Seven patients showed variants outside canonical positions. All of them needed molecular validation, with the exception of two patients, whose variants had previously been well characterized in the medical literature.ConclusionThis study shows the proportion of splicing variants in a cohort of IEI patients, providing their clinical phenotypic characteristics and the methodology used to validate the splicing defects. Based on the results, an algorithm is proposed to clarify when a splicing variant should be validated by complementary methodology and when, by contrast, it can be directly considered disease causing.